Synthesis, Spectroscopic and Thermal Analysis and Investigation of Dyeing Properties of o‐Hydroxy Schiff Bases and Their Metal Complexes - Özkınalı, Sevil; Yavuz, Şenol; Tosun, Tuğçe; Ali Köse, Dursun; Gür, Mahmut; Kocaokutgen, Hasan (Wiley, 2020)
Abstract Two series of new Schiff base metal complexes (Cu(II), Ni(II), Co(II), Mn(II), Zn(II)) were synthesized and used to study their fastness and thermal properties. All of the dyes were applied on cotton, polyester and cellulose acetate fabrics as reactive dyes by using temperature and 1 : 20 Flotte ratio. Washing, rubbing and light fastness was investigated by ISO 105‐C06 A2S, TS EN ISO 105‐X12 and ISO 105‐B02 methods, respectively and obtained very well to excellent results. Structures of the metal complex dyes were elucidated by IR, UV‐Vis, 1 H‐NMR, 13 C‐NMR, mass spectroscopic techniques, magnetic susceptibility measurements, elemental analysis, and thermal analysis. Spectroscopic results indicate that all of the complexes adopt octahedral geometry. Also the results indicate that the complexes are formed by the binding of a metal ion with two Schiff bases by using two >C=N‐ groups, two hydroxyl groups and two aqua ligands. In the present study, for the first time, fabrics were dyed with Schiff bases and metal complexes, and then, their fastness analyses were carried out and were obtained fine results.
Keywords: Schiff Base; Thermal Analysis; fastness properties; o-hydroxy; Metal Complexes; dyes